2020
DOI: 10.3390/ma13112510
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Mechanical Properties of Glass-Ionomer Dental Cements: A Review

Abstract: This paper reviews the strategies that have been reported in the literature to attempt to reinforce glass-ionomer dental cements, both conventional and resin-modified. These cements are widely used in current clinical practice, but their use is limited to regions where loading is not high. Reinforcement might extend these applications, particularly to the posterior dentition. A variety of strategies have been identified, including the use of fibres, nanoparticles, and larger particle additives. One problem rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
59
0
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(74 citation statements)
references
References 90 publications
5
59
0
10
Order By: Relevance
“…Therefore, the self-adhesive properties of glass ionomer are advantageous in the treatment of caries in the elderly. The mechanical properties of conventional glass ionomers are the worst among all [ 42 ]. The hardness and long-term wear of modified high-viscosity glass ionomer and resin-modified glass ionomer are far lower than the conventional ones [ 43 ].…”
Section: Currently Available Restorative Materials For the Elderlymentioning
confidence: 99%
“…Therefore, the self-adhesive properties of glass ionomer are advantageous in the treatment of caries in the elderly. The mechanical properties of conventional glass ionomers are the worst among all [ 42 ]. The hardness and long-term wear of modified high-viscosity glass ionomer and resin-modified glass ionomer are far lower than the conventional ones [ 43 ].…”
Section: Currently Available Restorative Materials For the Elderlymentioning
confidence: 99%
“…Applications include as liners and bases, full restorative materials, luting cements, pit and fissure sealants, and orthodontic adhesives [1,2]. In their conventional version, they are prepared by reaction of special basic glass powders with aqueous solutions of polymeric acids, such as poly(acrylic acid), acrylic acid-maleic acid copolymer, or the copolymer of 2methylene butanedioic acid with propenoic acid [3]. They are also available as resin-modified materials, where there is an additional monomer, usually 2-hydroxyethyl methacrylate.…”
Section: Introductionmentioning
confidence: 99%
“… 31 Studying scanning electron microscopy confirmed that the addition of nanoparticles reduced porosity, with no differences between the materials. 22 Therefore, it seems that the addition of BCNCs can fill spaces in the defects and impede the dissemination of previously present pores by blocking their paths, which in turn stops the pores from forming cracks and improves the DTS of RMGICs. It has been shown that an improvement in this property is hardly achievable in GICs.…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies have been performed to investigate various mechanical properties of RMGICs, 19 20 21 22 no research has been conducted to assess the effect of bacterial cellulose nanocrystals (BCNCs) on mechanical properties of RMGICs. Therefore, the purpose of this study was to evaluate the effect of BCNCs in three volumetric masses of 0.3, 0.5, and 1 wt% on the mechanical properties of RMGICs.…”
Section: Introductionmentioning
confidence: 99%